2015
DOI: 10.1016/j.jinteco.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity premia and interest rate parity

Abstract: Risk-free assets denominated in US currency not only o¤er a pecuniary return, but also provide transactions services, both nationally and internationally. Accordingly, the responses of bilateral US dollar exchange rates to interest rate shocks should di¤er substantially with respect to the (US or foreign) origin of the shock. We demonstrate this empirically and apply a model of liquidity premia on US treasuries originating from monetary policy implementation. The liquidity premium leads to a modi…cation of unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…These results are confirmed under a regime with the nominal policy rate at the ZLB. Here, a decline in the real policy rate is induced by the fixation of the nominal policy rate and leads to large This is shown by Bredemeier et al (2020), who further provide consistent empirical evidence on changes in liquidity premia after unanticipated monetary policy announcements, and by Linnemann and Schabert (2015), who find that liquidity premia help explain observed exchange rate responses to monetary policy shocks. Notably, our model with the liquidity premium also implies that an increase in a labor income tax rate at the ZLB leads to contractionary effects, whereas a model without the liquidity premium paradoxically predicts expansionary effects (as in Eggertsson, 2011).…”
Section: Introductionmentioning
confidence: 60%
“…These results are confirmed under a regime with the nominal policy rate at the ZLB. Here, a decline in the real policy rate is induced by the fixation of the nominal policy rate and leads to large This is shown by Bredemeier et al (2020), who further provide consistent empirical evidence on changes in liquidity premia after unanticipated monetary policy announcements, and by Linnemann and Schabert (2015), who find that liquidity premia help explain observed exchange rate responses to monetary policy shocks. Notably, our model with the liquidity premium also implies that an increase in a labor income tax rate at the ZLB leads to contractionary effects, whereas a model without the liquidity premium paradoxically predicts expansionary effects (as in Eggertsson, 2011).…”
Section: Introductionmentioning
confidence: 60%
“…2. Linnemann and Schabert (2015) find with their theoretical model a delayed response of the exchange rate mainly for a monetary policy shock originated in the United States, what they explain with liquidity premia on short-term treasuries.…”
Section: Resultsmentioning
confidence: 66%
“…In their model, forward guidance does not foster recovery, but only leads to increases in risk premia in their setting, which relates to the rise in liquidity premia implied by our model. A liquidity premium stemming from eligibility of certain assets in open market operations (which we apply for the analysis of forward guidance effects) has been shown by Linnemann and Schabert (2015) and Bredemeier et al (2017) to explain the observed delayed overshooting of exchange rates and to reconcile theory and evidence on the role of monetary policy for the fiscal multiplier, respectively.…”
Section: Introductionmentioning
confidence: 73%